Recent Progress in Reverse Osmosis (RO) Science and Technology - Ismail, A. F.; Khulbe, K. C.; Matsuura, T. (Journal of Applied Membrane Science & Technology, 2017)
While writing a book on reverse osmosis, it was realized that there had been remarkable progress in recent years in reverse osmosis science and technology. This is a brief summary in which many aspects of RO are discussed, including membrane material and membrane fabrication, membrane characterization, membrane transport, RO module, RO system design, economics, membrane fouling, RO applications and RO/NF membranes for nonaqueous system.Â 